DIMENSI KEPENTINGAN UMUM DALAM MEMBERIKAN HAK GUNA USAHA DI ATAS TANAH ULAYAT MASYARAKAT ADAT - St. Mahmud Syaukat (Universitas Pamulang, 2016)
With the nature that is so important, the soil was ranked first most potential conflict both vertical conflict (conflict between the residents and the authorities) and horizontal conflicts (conflicts among fellow citizens). Therefore a government of a country should be able to put politics pertanahannya law precisely by considering all sides of the state of society so that potential conflicts as mentioned above can be minimized. Against that government of the Republic of Indonesia after the win independence from the Dutch, trying to land reform and political building a new national land law by changing land laws in force earlier, Agrarisch Wet (Stb 1870-55) was considered not appropriate with the personality of the Indonesian nation. Hence was born the Act No. 5 of 1960 (BAL No.5 / 1960), the Law on Agrarian, hereinafter referred to as UUPA. The focus of the problem in this research is the dimension of Public Important Giving Hak Guna Usaha (HGU) Above Communal Land of Indigenous People, research conducted with secondary data are descriptive qualitative research shows the first, very important to the principle of general interest not give customary land both, would need to be established specifically about the provisions of lands which have positive implications for the public interest.Keywords: Publik Interest, HGU, Communal Land